A tutorial on the globally monotonic tracking control problem with geometric techniques - Ntogramatzidis, Lorenzo; Tregouet, J.; Schmid, R.; Ferrante, A. (2016)
In this paper we present a method for designing a linear time invariant (LTI) state-feedback controller to monotonically track a constant step reference at any desired rate of convergence for any initial condition. This framework shows that for MIMO LTI systems the objectives of achieving a rapid settling time, while at the same time avoiding overshoot and/or undershoot, are not necessarily competing objectives.